Association analysis of apoptosis-related gene Caspase3, integrin α subunit 1 and glutathione sulfur transferase M1 gene polymorphisms and susceptibility to gastric cardia carcinoma - Wang, Rui; Zhang, Zetian; Li, Duo; Wu, Na; Peng, Zhao (Journal of Medical Biochemistry, 2022)
Objective: To explore the association of polymorphisms of apoptosis-linked genes caspase3 (CASP3), integrin α subunit 1 (ITGA1), glutathione sulfur transferase M1 (GSTM1) with susceptibility to gastric cardia carcinoma (GCC). Methods: From February 2016 to March 2018, selection of 113 GCC patients was as the gastric cancer (GC), and selection of 75 patients without gastric disease was as the control. Detection of CASP3, ITGA1 and GSTM1 gene polymorphisms in patients’ peripheral blood was to analyze their association with GC. Division of the GC was into the good prognosis and the unpleasing prognosis in the light of the survival of patients after surgery of 3 years, and the predictable value of gene polymorphisms of CASP3, ITGA1 and GSTM1 in GCC patients was analyzed. Results: CASP3 gene rs12108497 locus, ITGA1 gene rs1862610 locus and GSTM1 genotype of the GC and the control were in accord with Hardy-Weinberg equilibrium (P > 0.05); The detection rate of CASP3 gene rs12108497 locus TC/CC type, ITGA1’s gene rs1862610 locus AC/AA type and GSTM1 blank type in the GC was elevated vs. the control (P < 0.05); Logistic regression analysis manifested smoking, anxiety, helicobacter pylori infection, family history of gastrointestinal tumor, combination with chronic gastric disease, CASP3 gene and GSTM1 gene polymorphism were risk factors for GC (P < 0.05); Stratification was in the light of individual smoking status, discovering that the detection rates of CASP3 gene rs12108497 locus TC/CC type, ITGA1 gene RS1862610 locus AC/AA type and GSTM1 blank type in the smoking were crucially augmented vs. the smoking (P < 0.05); The detection rates of CASP3 gene rs12108497 locus TC/CC type, ITGA1 gene rs1862610 locus AC/AA type and GSTM1 blank type in the death were augmented vs. the survival (P < 0.05); Combined detection of CASP3, ITGA1 and GSTM1 gene polymorphisms was provided with predictive value for GCC’s prognosis (P < 0.05). Conclusion: CASP3 and GSTM1 genes are susceptibility genes for GCC, which might be associated with the occurrence of GCC in smoking patients, and the joint detection of multiple genes is provided with predictive value for patients’ prognosis.